Relación maestro-estudiante en la resolución de problemas de movimiento: una visión epistemológica de los conceptos de posición, velocidad y aceleración - Moreno, Norman; Agudelo, A (Revista Científica, 2011)
The student teacher relationship in problem solving as teaching strategy is marked by the relationships that show students and teachers in the use of key concepts for the study of motion, which implies an epistemological root. In addition, the characterization of a typology of concepts in physics from epistemological criteria that vary according to philosophical and through a hermeneutic method basis (Distil information) semantic fields can be generated in contrast to the notions of concept raised by Bunge (1985),a glimpseinto the relationships between teachers and students in terms of the appropriation ofconcepts of movement in the context of professional training in engineering.